Optimization of multiple piezoelectric magnetic fans for electronic cooling system - Abdul Razak, Fadhilah (2020)
Air cooling system for electronics is still preferable due to its simplicity and reliability. To date, some researches on air cooling showed that a piezoelectric fan is more efficient than natural convection with minimum power consumption. However, a single piezoelectric fan can only cover a small cooling area and more power might be consumed if multiple piezoelectric fans are applied. A multiple piezoelectric magnetic fan (MPMF) has proven to have a high potential to replace the existing rotary fan. Initially, the MPMF was designed in line/array (APMF). However, the deflection of the MPMF needs to be improved in fundamental analysis and validated by the experimental data from previous studies. Hence, the first objective of the study is to propose a new mathematical model for MPMF to include the location of magnet and distance between magnets to length ratio. A centripetal force is introduced as the contributing parameter to the equation of deflection of a radial piezoelectric magnetic fan (RPMF). The second objective is to optimize the multiple piezoelectric magnetic fan parameters using Response Surface Method (RSM). The experimental setup consisted of two divisions; parameters optimization and thermal analysis. The theoretical results of the fan deflection were compared with experimental data and the thermal performance of the proposed RPMF was compared with the benchmarked paper. The results showed that an optimal magnet location was on the Mylar blade, 44mm from the origin (63.8% of original length). The new location of magnet has led to increment of Reynolds Number to 924. The distance between magnets to length ratio is in the range of 14.5mm to 15.6mm (21%-22.6% of the fan length). By fixing the distance between magnets at 14.5mm, the resonant frequency and deflection of RPMF and APMF were 42.66Hz, 11.6mm and 40.68Hz, 9.4mm respectively. By varying the orientation of MPMF, the Reynolds number of RPMF was improved 32% compared to APMF. The heat convection coefficient increased by 8.07% to enhance the heat transfer performance by 8.06%. The thermal resistance reduced by 7.6% which led to 5% increment of overall thermal efficiency. In conclusion, the relocation of magnet has improved the overall performance of MPMF. The RPMF has been found to have a better cooling performance compared to APMF. Thus, RPMF has a high potential to be applied in electronics cooling system.